Characterization of the B cell response to Leishmania infection after anti-CD20 B cell depletion - Bockenstedt, Marie M (Int J Clin Exp Pathol, 2015)
Anti-CD20 depletion therapies targeting B cells are commonly used in malignant B cell disease and autoimmune diseases. There are concerns about the ability of B cells to respond to infectious diseases acquired either before or after B cell depletion. There is evidence that the B cell response to existing or acquired viral infections is compromised during treatment, as well as the antibody response to vaccination. Our laboratory has an experimental system using co-infection of C3H mice with both Leishmania major and Leishmania amazonensis that suggests that the B cell response is important to healing infected mice. We tested if anti-CD20 treatment would completely restrict the B cell response to these intracellular pathogens. Infected mice that received anti-CD20 B cell depletion therapy had a significant decrease in CD19(+) cells within their lymph nodes and spleens. However, splenic B cells were detected in depleted mice and an antigen-specific antibody response was produced. These results indicate that an antigen-specific B cell response towards intracellular pathogens can be generated during anti-CD20 depletion therapy.